Population dynamics of dominant demersal fishes caught in Tambelan Islands waters, Riau Archipelago Province - YOVITNER phdmrk@gmail.com; FAHMI FAHMI (Society for Indonesian Biodiversity, 2012)
Yonvitner, Fahmi. 2012. Population dynamics of dominant demersal fishes caught in Tambelan Islands waters, Riau Archipelago Province. Biodiversitas 14: 200-204. The population of demersal fishes tends to be decline in the last few decades. The decline was due to the increased of intensive catches, fishing effort and illegal fishing practices. This study aimed to examine aspects of population dynamics such as mortality, recruitment, opportunity capture and population estimation. The study was conducted in six locations at Tambelan waters, on 4-16 November 2010. Collected data included the fish species, size and biomass catch. The analyses performed included mortality, recruitment, opportunity capture and population estimates (VPA). The data indicated that the Genus of Nemipterus and Lutjanus possess the highest total mortality rate that was respectively 1.62 and 2.55. The highest recruitment presentation of the population which has an annual period as Pentapodus was 16%. Catch opportunities tend to be higher than actual fishing, while the alleged biomass of steady state conditions reached 12.2 tons/yr.